On the possibility of using Ramie – A natural material in cost-effective low threat body armours. Issue 4 (June 2022) - Sen, Subhajit; Shaw, Amit; Adhikari, Basudam
Low intensity clashes have become the emerging crisis in society. In such situations, the protective vests worn by the law enforcing personnel are generally exposed to stabbing and low velocity impact from splinters. The present study is an attempt to explore the potential of Ramie, a natural fibre, to be used in body armours designed for relatively lesser threat (compared to military operations) encountered in low intensity conflict areas. Cultivation of Ramie plant to the preparation of Ramie fabric – the entire process is performed in a laboratory setup. Experiments (uniaxial tension test, direct shear test, yarn pull-out test, etc.) are conducted to characterize the stress–strain behaviour and inter-yarn friction of Ramie. The ballistic responses of single and multi-layered Ramie fabric targets are numerically investigated via FEM. In order to understand where Ramie stands with respect to Kevlar (a commonly used para-aramid synthetic fabric), the response of a single layer Kevlar target under similar circumstances (i.e. target size, boundary conditions, projectile types and impact velocities) is taken as the benchmark. Through the series of numerical simulations, the advantage and limitations of Ramie vis - a ´- vis Kevlar are brought to an extent.